2016
DOI: 10.1007/s12551-016-0218-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic light scattering: a practical guide and applications in biomedical sciences

Abstract: Dynamic light scattering (DLS), also known as photon correlation spectroscopy (PCS), is a very powerful tool for studying the diffusion behaviour of macromolecules in solution. The diffusion coefficient, and hence the hydrodynamic radii calculated from it, depends on the size and shape of macromolecules. In this review, we provide evidence of the usefulness of DLS to study the homogeneity of proteins, nucleic acids, and complexes of protein-protein or protein-nucleic acid preparations, as well as to study prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
953
0
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,400 publications
(996 citation statements)
references
References 91 publications
27
953
0
16
Order By: Relevance
“…DLS measures the fast (nanosecond) fluctuations of scattered light intensity by particles in solution as they diffuse due to Brownian motion, and determines the translational diffusion coefficient. The translational diffusion coefficient can be used to calculate the particle hydrodynamic radius (R h ) and size using equations derived from the first principles of classical physics (Stetefeld, McKenna, & Patel, 2016). Scratches on the glass bottom of microwell plates and dust particles cause large and artifactual light scattering effects.…”
Section: Dynamic Light Scattering (Dls) In 384-well Plate Format To Dmentioning
confidence: 99%
“…DLS measures the fast (nanosecond) fluctuations of scattered light intensity by particles in solution as they diffuse due to Brownian motion, and determines the translational diffusion coefficient. The translational diffusion coefficient can be used to calculate the particle hydrodynamic radius (R h ) and size using equations derived from the first principles of classical physics (Stetefeld, McKenna, & Patel, 2016). Scratches on the glass bottom of microwell plates and dust particles cause large and artifactual light scattering effects.…”
Section: Dynamic Light Scattering (Dls) In 384-well Plate Format To Dmentioning
confidence: 99%
“…[5] A large variety of experimental and theoretical methods has been used in the past to investigate the shape and form of unfolded macromolecules, such as static-and dynamic light scattering [6] or viscosimetry, dating back to the fundamental investigations of Staudinger. [7] Modern methods to probe e. g. distance-relations between the ends of macromolecules including methods such as fluorescence resonance energy transfer (FRET), [8] triplet/triplet-energy transfer (TTET), [9] or ESR-spectroscopy [10] provide an average picture of chain extension. Especially the largely growing field of singlechain folded macromolecules, [5,11] where an individual chain of a synthetic macromolecule is folding into a singular nanoparticle, [12] is still elusively explored, because of a lack of specific methods to probe the folding of individual polymer based nanoparticles.…”
Section: Probing Polymer Chain Conformation and Fibril Formation Of Pmentioning
confidence: 99%
“…The quaternary structure and homogeneity of the purified protein was evaluated by dynamic light scattering (DLS). The technique estimates the molecular weight and size distribution of the protein via measurements of its diffusion in solution over time . A “distribution by volume analysis” of the protein (stock solution) indicated that there was essentially only a single species of protein present (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…The technique estimates the molecular weight and size distribution of the protein via measurements of its diffusion in solution over time. 18 A "distribution by volume analysis" of the protein (stock solution) indicated that there was essentially only a single species of protein present ( Figure 2b). The hydrodynamic diameter of the protein was estimated to be 7.14 nm, corresponding to the molecular weight of a dimer (84 KDa).…”
Section: Evaluation Of Folding and Structural Homogeneity Of Tcfppsmentioning
confidence: 99%